EVALUATING COVID-19’ TAX INCENTIVES: MEASURING THE POLICY EFFECTIVENESS AND PROSPECTIVE POLICY ANALYSIS ON THE EXTENDED PROVISION - Susilawati, Neni; Ramadhena, Citra Yadin; Syahputri, Mayang Permatasari; Wardhani, Regina Canda (Sebatik, 2022)
Policy-making strength is an integral part of the government vigor. When policies fail, monetary and fiscal costs would significantly increase. Covid-19's Tax Incentive is one of the costs that must be incurred due to the Covid-19 pandemic. However, the absorption of this tax incentive has not been optimal, as indicated by the large gap between the budget and the realization of the tax incentives absorption. This research's aims are to evaluate the policy effectiveness of the Covid-19's tax incentives and analyzing the prospective policy of extended provision based on the evidences. This qualitative research was conducted with literature study as data collection technique. The qualitative data was processed using NVivo software. As the result, the policy aims of Covid-19's Tax Incentives are to maintain the economic growth stability, maintain people's purchasing power, maintain the productivity of certain sectors, support the handling of the Covid-19's impact, and maintain stock market stability. Covid-19's Tax Incentives provides quite effective results in dealing with the negative impacts of the pandemic. Most of the tax incentive policy targets appear to have been achieved, step by step. However, some policies have not been optimally absorbed. The provision of tax incentives can have a positive impact on the economy. However, on the other hand, evidence of increasing national debt can be an indicator that these incentives can also harm financial conditions. The government must be more effective. According to the data, not all types of tax incentives have a level of leverage for national economic recovery.